Responding to Survivors of Intimate Partner Homicide in Black Communities - Bent-Goodley, Tricia B. (Homicide studies, 2025)
While there has been increasing attention given to understanding intimate partner violence homicide, little has been done to address how to support survivors of intimate partner violence homicide. This paper explores perceptions of the needs of survivors of intimate partner violence homicide through 22 focus groups which included 128 participants identifying as Black or African American. Of those, 28 identified as survivors of intimate partner violence and 26 identified as providers. The findings reinforce addressing the needs of intimate partner violence homicide survivors from a holistic, culturally responsive, and trauma-informed lens. Implications on how to address these needs are discussed.